The Effect of Social Media Marketing and E-Service Quality on the Decision to Choose Private Tutoring Services "Be Smart Student" Mediated by Brand Trust - Ismawati, Putri; Yahya, Adibah; Putra, Hamzah Muhammad Mardi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to determine and analyze the influence of social media marketing and e-service quality on the decision to choose Private Lesson "Be Smart Student" mediated by brand trust. The research uses quantitative method and data collection technique using g-form questionnaire for 314 respondents (parents) of students. The data analysis technique uses path analysis to determine the fit of the structural equation model with SmartPLS 4.1.0. The results conclude: Social media marketing has a positive and significant effect on choosing decisions; E- Service Quality has a positive and significant effect on choosing decisions; Brand trust has a positive and significant effect on choosing decisions; Social media marketing has a positive and significant effect on brand trust; E-Service Quality has a positive and significant effect on brand trust; Social media marketing has a positive and significant influence on choosing decisions mediated by brand trust; and E-Service Quality has a positive and significant effect on choosing decisions mediated by brand trust. The results have implications for efforts to improve marketing strategies through applying digital platforms to market institutional programs and learning processes.